Identification of QTL for Grain Size and Shape on the D Genome of Natural and Synthetic Allohexaploid Wheats with Near-Identical AABB Genomes - Yan, Lei; Liang, Fei; Xu, Huanwen; Zhang, Xiaoping; Zhai, Huijie; Sun, Qixin; Ni, Zhongfu (Frontiers in Plant Science, 2017)
Abstract Grain size and shape associated with yield and milling quality are important traits in wheat domestication and breeding. To reveal the genetic factors on the D genome that control grain size and shape variation, we conducted analysis of quantitative trait loci (QTL) using the F2 and F2:3 populations derived from a common allohexaploid wheat line TAA10 and a synthetic allohexaploid wheat XX329, which have near-identical AABB genomes and different DD genomes. Based on genotyping using wheat 660K single nucleotide polymorphism (SNP) array, TAA10 and XX329 exhibited 96.55%, 98.10% and 66.26% genetic similarities of A, B and D genomes, respectively. Phenotypic evaluation revealed that XX329 had higher thousand grain weight, grain length, width, area and perimeter than TAA10 across all environments, and the grain yield per plot of XX329 increased by 17.43%-30.36% compared with that of TAA10 in two environments. A total of nine environmentally stable QTL associated with grain size and shape were mapped on chromosomes 2D and 7D and verified using near isogenic lines (NILs), with the synthetic allohexaploid wheat XX329 contributing favorable alleles. Notably, a novel QTL QTgw.cau-2D controlling grain weight was first identified from the synthetic allohexaploid wheat, which may be a more desirable target for genetic improvement in wheat breeding. Collectively, these results provide further insights into the genetic factors that shaped the grain morphology during wheat evolution and domestication.